CADRE Quick-Look: Homeland Security-NORTHCOM's Coalition War - Conway, John L. (2005)
The United States has entered into a new phase in its military history, passing quickly through "joint" warfare into the realm of "coalition" warfare. Indeed, it is postulated that coalition warfare will be the only way we will conduct future fights. Coalition warfare has many facets: it involves the blending of different cultures, multiple languages dialects, and disparate weapon systems, as well as differing perceptions of end states and how to achieve them. In the wake of 9/11, HQ Northern Command (HQ NORTHCOM) was created to accomplish two goals: to provide the military response to attacks within the United States at the request of the newly formed Department of Homeland Security (DHS) and to perform the National Security mission of air defense of the North American continent through HQ NORAD. As Steve Flynn from the Council on Foreign Relations has observed: "We do National Security very well and Homeland Security very badly." NORTHCOM's National Security role is, for the most part, a continuation of NORAD's successful alliance with Canada; a 50 year relationship that has transcended the Cold War and has moved toward the new air defense realities i.e., defense within the borders as well as outside them, post 9/11. In its Homeland Security role however, NORTHCOM is part of a "coalition of the willing" much like the one CENTCOM fulfills. But unlike CENTCOM's dozen or so international coalition partners, NORTHCOM's are the numerous federal, state and local agencies, bureaus and organizations involved in Homeland Security; many more partners than any international coalition would ever envision. For example, just within the law enforcement community, there are 600,000 police in 18,000 police departments, and 31,000 separate sheriffs departments. The original document contains color images.